Deep-Sea decapod crustaceans (Caridea, Polychelida, Anomura and Brachyura) collected from the Nikko Seamounts, Mariana Arc, using a remotely operated vehicle “Hyper-Dolphin” - Komai, Tomoyuki; Tsuchida, Shinji (Zootaxa, 2014)
Samples and images of deep-water benthic decapod crustaceans were collected from the Nikko Seamounts, Mariana Arc, at depths of 520–680 m, by using the remotely operate vehicle “Hyper-Dolphin”, equipped with a high definition camera, digital camera, manipulators and slurp gun (suction sampler). The following seven species were collected, of which three are new to science: Plesionika unicolor n. sp. (Caridea: Pandalidae), Homeryon armarium Galil, 2000 (Polychelida: Polychelidae), Eumunida nikko n. sp. (Anomura: Eumunididae), Michelopagurus limatulus (Henderson, 1888) (Anomura: Paguridae), Galilia petricola n. sp. (Brachyura: Leucosiidae), Cyrtomaia micronesica Richer de Forges & Ng, 2007 (Brachyura: Inachidae), and Progeryon mus Ng & Guinot, 1999 (Brachyura: Progeryonidae). Affinities of these three new species are discussed. All but H. armarium are recorded from the Japanese Exclusive Economic Zone for the first time. Brief notes on ecology and/or behavior are given for each species.